The complete guide to national symbols and emblems - Minahan, James (Greenwood Press, 2010)
These two volumes offer a collection of flags, seals, and symbols used every day around the world. This guide brings a concise and updated order to the national symbols of the independent nations of the world, as well as a representative sample of dependent territories attempting to obtain wider recognition. In addition to the national flag, each entry provides fundamental and cultural background information, including basic demographic data, the national anthem, flora and fauna, cuisine, national resources, sports teams, national heroes or personifications, and significant events that relate to establishment of the nation's identity. Volume Two includes an appendix of relevant international organizations and a selected bibliography, as well as a subject index that facilitates cross-reference access.